2008
DOI: 10.1161/circulationaha.107.747329
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Arteriolar Narrowing in Low-Birth-Weight Children

Abstract: Background-Cardiovascular disease may have its origins in utero, but the influence of in utero growth on microvascular structure in children is unknown. We hypothesized that poor in utero growth is associated with narrower arteriolar caliber, which may help explain the established association of low birth weight with hypertension and cardiovascular disease in adulthood. Methods and Results-We examined the relation of birth weight and other markers of in utero growth to microvascular caliber in the retina in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
87
2
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(105 citation statements)
references
References 50 publications
14
87
2
2
Order By: Relevance
“…31 The relatively small sample size and the issue of statistical power in this study highlight the need for larger twin studies of more precise analysis in this area. Because our cohort was not large, some of the null findings reported may partially reflect inadequate statistical power, although the lack of influence of birth parameters on retinal venular caliber is consistent across all twin subtypes and is in agreement with estimates from singletons 7,8 and with previous observations of no association of venular caliber with blood pressure. 32,33 The association between gestational duration and retinal arteriolar caliber in this study was not independent of birth weight.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…31 The relatively small sample size and the issue of statistical power in this study highlight the need for larger twin studies of more precise analysis in this area. Because our cohort was not large, some of the null findings reported may partially reflect inadequate statistical power, although the lack of influence of birth parameters on retinal venular caliber is consistent across all twin subtypes and is in agreement with estimates from singletons 7,8 and with previous observations of no association of venular caliber with blood pressure. 32,33 The association between gestational duration and retinal arteriolar caliber in this study was not independent of birth weight.…”
Section: Discussionsupporting
confidence: 87%
“…Twin studies provide insights into whether the association between birth size and retinal vascular structure reported in previous studies in children and adults 7-10 is because of shared environment (eg, maternal factors), common genetic factors, or other pathways associated with individual twins. Thus, our findings add further insights into studies from a 6-year-old singleton childhood population 7 and the Atherosclerosis Risk in Communities Study (general population aged 51 to 72 years), which found that lower birth size (eg, birth weight) was associated with narrower retinal arterioles. 8 We found that the overall associations strengthened with increased magnitude in models with further adjusting for mean arterial blood pressure, BMI, and child height, reflecting that it was not the individual-specific differences in these later child factors that contributed to the association between shorter birth length and narrower arteriolar caliber.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Another possible explanation for the thinning of the RNFL in the sectors except for the temporal sector is artifacts from the vessels. It has been reported that children with low birth weight have narrower arterioles, 19 and arteriolar caliber is positively correlated with RNFL thickness and macular thickness. [20][21][22] Therefore, narrower vessels in preterm children compared with normal full-term controls could induce artifactually thinned RNFL measured by OCT. 23 Further histologic studies could help to clarify this idea.…”
Section: Variablementioning
confidence: 99%
“…However, the cross-sectional nature of these studies does not allow for causal inferences. A recent study also demonstrates that poor growth in utero may have an adverse influence on retinal vasculature in children (29).…”
Section: Measures Of Vascular Healthmentioning
confidence: 95%